Autopsy profiles of malpractice cases - (:unkn) unknown (ELSEVIER SCI LTD, 2009)
Claims for medical malpractice and the number of lawsuits filed thereafter are increasing in Turkey as is the case throughout the world. In the present study all files issued by the associated boards of the Council of Forensic Medicine between 2001 and 2005 were studied and of those, 525 death cases in which there was a medical malpractice claim were included. 303 of the cases (57.7%) were male, 215 (41%) were female, while no gender was mentioned in seven cases (1.3%). The age of the subjects ranged between 0 and 90, with an average of 26.8. 147 cases (28%) were related to Emergency Units. 92% of the cases (482 cases) were resolved in the Council of Forensic Medicine, Ministry of Justice. 167 of the resolved cases were concluded as medical malpractice. (C) 2008 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: Medical malpractice; Autopsy; Forensic medicine